1982
DOI: 10.1161/01.atv.2.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Increased apoprotein B in very low density lipoproteins of patients with peripheral vascular disease.

Abstract: Lipoproteln compositional studies were carried out in 20 patients with atherosclerotic peripheral vascular disease. Twelve of these patients were normollpldemlc, the other eight, hypertriglycerldemic. Ten normollpldemlc and 10 hypertriglyceridemlc age-matched subjects were used as controls. High density lipoprotein cholesterol levels were markedly reduced in the hypertriglyceridemlc sub|ects, both with (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Among the "negative" risk factors for atherosclerosis, we found only apo A-ll a significant parameter. Our results were similar to those reported by Whayne et al 18 and Riesen et al 17 in patients with CVD, as well as to the results of Franceschini et al 9 in PVD patients in that we found no significant difference in HDL-C between PVD patients and controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the "negative" risk factors for atherosclerosis, we found only apo A-ll a significant parameter. Our results were similar to those reported by Whayne et al 18 and Riesen et al 17 in patients with CVD, as well as to the results of Franceschini et al 9 in PVD patients in that we found no significant difference in HDL-C between PVD patients and controls.…”
Section: Discussionsupporting
confidence: 93%
“…Mertz 20 considered the atherosclerosis index (LDL-C/HDL-C) as the most prominent indicator for peripheral atherosclerosis. PVD patients and controls were well separated by VLDL-apo B/VLDL-C. 9 In this and other studies, however, there were no calculations on related subjects concerning specificity, sensitivity, or rate of misclassification using one or several parameters as discriminators. In this report we tried to find out which single parameter might best reflect peripheral atherosclerosis.…”
mentioning
confidence: 55%
“…Also among the PVD patients, significantly higher blood levels of Apo B were measured, with total cholesterol concentrations that tended to be lower,.. Ns, than for the controls. This result is similar to findings of other authors (19,36,56) for PVD patients not selected according to their clinical stages. The Apo B increase could also suggest a change in the lipoprotein composition of LDL-C and VLDL-, with the appearance of Apo B-icher lipoproteins and, probably, more atherogenesis (36).…”
Section: No Significant Difference Between Pvd Patientssupporting
confidence: 92%
“…The data concerning other lipidic parameters such as LDL-C and Apo still seem contradictory (1,(19)(20)(21)36). However, the discrepancies found in literature might be due to a failure to apply strict selection ' criteria to the patients enrolled in the various dinical studies concerning this disease.…”
mentioning
confidence: 99%
“…According to studies of Franceschini et al (6), increased concentrations of apolipoprotein B in VLDL are associated with peripheral vascular disease. Therefore, the determination of VLDL apolipoprotein B may be of special clinical and epidemiological significance.…”
Section: Introductionmentioning
confidence: 99%